Modelagem e controle do conversor DAB para interface entre banco de baterias e sistema elétrico de potência - Costa, Pablo Fernando Soardi (2017)
This Master's Dissertation presents the development of a Dual Active Bridge (DAB) converter for charging a battery bank, which is connected to a DC bus, which is connected to the electric power system by means of an inverter. The purpose of the proposed DAB converter is to charge the battery bank through the Constant Current / Constant Voltage (CC / CV) method. For the choice of the topology employed a brief study of topologies with high voltage gain, galvanic isolation and bidirectionality in the power flow was performed. In addition, a study on the main types of energy accumulators was also carried out, where among the technologies studied we can mention supercapacitors, flywheels systems and Li-ion batteries. After defining the topology of the DC-DC converter to be adopted, an in-depth analysis of the DAB converter was performed, describing the operation steps, modulation types commonly applied to this topology, as well as the zero voltage switching range - ZVS). The mathematical model of the converter will also be analyzed through the Linearization of the Output Current, which is used for the design of the controllers. Once the mathematical model has been defined, the designs of the controllers used in the work are carried out, a current controller and a voltage controller, which act independently at each step during the battery bank loading process. Initially, the current controller imposes a constant current of 20% CAh on the batteries until they reach 54 V, the value of the equalization voltage. At this moment the voltage control loop starts operating maintaining constant voltage (with voltage equalization value) on the battery bank until the current is equal to 2% of the C. Then the battery voltage is reduced to 48 V, entering the float mode, thus completing the process of charging the battery bank. Experimental results are presented in order to verify the performance of the DAB converter.